Practical ex-chiral-pool methodology for the synthesis of dopaminergic tetrahydroindoles - Gmeiner, Peter; Hübner, Harald; et al. (Tetrahedron, 2004)
Chemo- and regioselective transformations of asparagine gave access to optically active 5- and 6-amino tetrahydroindolizines when the 3-aminobutyrolactone (S)-2 was employed as a key intermediate. The target compounds were approached by a sequential and regiocontrolled bis-electrophilic attack in the positions 2 and 3 of the pyrrole ring system. Receptor binding experiments showed stereocontrolled receptor recognition leading to the D3 selective agonist (S)-8 with D3 binding that is comparable to the natural neurotransmitter dopamine. © 2003 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.lphch.practi
Keywords: Aminobutyrolactone; Asparagine; Ex-chiral pool synthesis; Receptor binding